Psychology of athletes' dual careers: A state-of-the-art critical review of the European discourse. (May 2019) - Stambulova, Natalia B.; Wylleman, Paul
Abstract: Objectives: (a) To provide a state-of-the-art critical review of European dual career (DC) research (2015–2018, English language), (b) to position the current DC (psychological) research within the athlete career sport psychology discourse and within the European DC discourse, and (c) to identify research gaps and future challenges. These objectives were formulated after an appraisal of nine existing review-type papers contributed to the European DC discourse. Methodology: This review has been informed by the Preferred Reporting Items for Systematic Review and Meta Analyses (Moher, Liberati, Tetzlaff, Altman, & The PRISMA group, 2010) and recommendations on presenting results of the state-of-the-art critical review by Grant and Booth (2009). Results: Following an extensive literature search across several databases, 42 research papers were used for appraisal, synthesis, and critical analysis of the current DC research. Major tenets of the cultural praxis of athletes' careers (Stambulova & Ryba, 2013a, b ;2014 ) were used as a critical lens in the analysis. Conclusions: DC research contributes to and connects the European DC discourse and the athlete career sport psychology discourse. DC in sport and work, DC "costs", DC development environments, DC athletes' mental health and well-being, DC support and training of the support providers constitute the major gaps in current DC research. Filling these gaps presents future challenges for DC research to adequately support practice and policy making within the European DC discourse. Highlights: Forty two peer-reviewed dual career (DC) articles from 2015–18 were reviewed. Mapping and narrative syntheses revealed progress and gaps in current DC research. Tenets of cultural praxis of athletes' careers were used as a lens for critical reflections. European DC discourse and athlete career (psychology) discourse were found to overlap. DC term has been established, and a holistic lifespan perspective informed most studies.